Risk of Synchronous and Metachronous Colorectal Cancer: Population-Based Estimates in Denmark with Focus on Non-Hereditary Cases Diagnosed After Age 50. (June 2019) - Lindberg, L. J.; Ladelund, S.; Bernstein, I.; Therkildsen, C.; Nilbert, M.
Background and Aims: The risk of synchronous and metachronous colorectal cancer is influenced by heritable and environmental factors. As a basis for comparative studies, we provide population-based estimates of synchronous and metachronous colorectal cancer with a focus on non-heritable cases. Material and Methods: Based on data from national Danish cancer registers, we estimated the proportion of synchronous colorectal cancer and the incidence rates and risks for metachronous colorectal cancer in 28, 504 individuals, who developed 577 metachronous colorectal cancer above age 50. Results: Synchronous colorectal cancer was diagnosed in 1.3% of the cases. The risk of metachronous colorectal cancer was associated with sex, tumor location, and age with the strongest influence from the latter. The incidence rate ratios for metachronous colorectal cancer ranged from above 6 in patients below age 65 to <1–3.2 in patients above age 65. The absolute risk of metachronous colorectal cancer was ⩾10% in patients below age 65 and 1.0%–8.0% in patients above age 65. Conclusion: Individuals who develop sporadic, non-inherited colorectal cancer above age 50 are at a significantly increased risk of metachronous colorectal cancer with risk estimates that are strongly affected by age. This observation underscores the need for development of targeted surveillance in the most common clinical subset of colorectal cancer.